ADP Induces Blood Glucose Through Direct and Indirect Mechanisms in Promotion of Hepatic Gluconeogenesis by Elevation of NADH - Cao, Xinyu; Ye, Xiaotong; Zhang, Shuang; Wang, Li; Xu, Yanhong; Peng, Shiqiao; Zhou, Yang; Peng, Yue; Li, Junhua; Zhang, Xiaoying; Han, Xiao; Huang, Wen-ying; et al. (Frontiers in Endocrinology, 2021)
Extracellular ADP, a derivative of ATP, interacts with the purinergic receptors in the cell membrane to regulate cellular activities. This signaling pathway remains unknown in the regulation of blood glucose in vivo. We investigated the acute activity of ADP in mice through a peritoneal injection. In the lean mice, in response to the ADP treatment, the blood glucose was elevated, and pyruvate tolerance was impaired. Hepatic gluconeogenesis was enhanced with elevated expression of glucogenic genes (G6pase and Pck1) in the liver. An elevation was observed in NADH, cAMP, AMP, GMP and citrate in the liver tissue in the targeted metabolomics assay. In the primary hepatocytes, ADP activated the cAMP/PKA/CREB signaling pathway, which was blocked by the antagonist (2211) of the ADP receptor P2Y13. In the circulation, gluconeogenic hormones including glucagon and corticosterone were elevated by ADP. Insulin and thyroid hormones (T3 and T4) were not altered in the blood. In the diet-induced obese (DIO) mice, NADH was elevated in the liver tissue to match the hepatic insulin resistance. Insulin resistance was intensified by ADP for further impairment in insulin tolerance. These data suggest that ADP induced the blood glucose through direct and indirect actions in liver. One of the potential pathways involves activation of the P2Y13/cAMP/PKA/CREB signaling pathway in hepatocytes and the indirect pathway may involve induction of the gluconeogenic hormones. NADH is a signal for gluconeogenesis in the liver of both DIO mice and lean mice.